TECHNIQUES OF THE COMIC IN THE ARTISTIC WORLD OF SATIRE (Web of Teachers: Inderscience Research, 2024)
In this paper we address the definition of the concepts of humor and satire, as well as the analysis of various forms of satire realization in poetry and prose. The article raises the question of the relationship between satire, humor and the comic, which remains the subject of discussion and various interpretations among literary researchers. The author has attempted to identify methods and techniques that can be used to create a satirical effect.